Peningkatan Perilaku Hidup Bersih dan Sehat (PHBS) Melalui Penyuluhan dan Penanaman Tanaman Obat Keluarga (TOGA) - Eza Helyatha Begauvic; Sri Yenasari; Yepi Susnita; Raisa Amini; Sindi Mardatillah; Erlin Ady Kurnia; Lisa Aristantia; Umi Haniah; Putri Sartika; Oki Saputra; Ranti Ayu Anjelina; Eliva Paulia; Fitri Novitasari; Eka Dwiningsih; Esti Yustika Murni (JURNAL PENGABDIAN KADER BANGSA, 2025)
In order to implement the Higher Education Tri Dharma, especially community service, Kader Bangsa University Palembang organized a KKN program in Pengabuan Village, PALI Regency. This activity aims to assist the community in utilizing existing resources, with an emphasis on increasing awareness and practice of Clean and Healthy Living Behavior (PHBS). Through participatory and observational approaches, this activity aims to increase community awareness, especially those in Pengabuan Village, about the importance of Clean and Healthy Living Behavior for health and environmental cleanliness. The results show that there is community interest in the importance of health and environmental cleanliness because the outreach activities carried out received great attention. This Community service activities also identifies the challenges faced and provides recommendations for the development of future KKN programs